2014
DOI: 10.4236/health.2014.617267
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Children’s Body Mass Index and Parents’ Obesity and Socioeconomic Status: A Multilevel Analysis Applied with Luxembourg Data

Abstract: Obesity in children is a health crisis because the problem is increasing in most developed countries. This study measures the relationship between body mass index (BMI) of children aged 7 -12 years residing in Luxembourg and the weight and socioeconomic status of their parents. The data used are from the 2007 Socio-Economic Panel Liewen zu Lëtzebuerg/European Union-Statistics on Income and Living Conditions survey, which covers a population of approximately 10,000 people. The study sample includes 775 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
4
13
3
1
Order By: Relevance
“…This observation is in line with the results of other studies conducted in the United Kingdom [37], Luxembourg [21], and Germany [19], in which this association is explained with reference to the subjects’ ethnicity, the socio-economic level of families with an immigrant background, and the continuation of certain “obesogenic” habits and behaviours. Additionally, in our study, these factors could explain the high prevalence of OW among children with parents born outside Italy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is in line with the results of other studies conducted in the United Kingdom [37], Luxembourg [21], and Germany [19], in which this association is explained with reference to the subjects’ ethnicity, the socio-economic level of families with an immigrant background, and the continuation of certain “obesogenic” habits and behaviours. Additionally, in our study, these factors could explain the high prevalence of OW among children with parents born outside Italy.…”
Section: Discussionsupporting
confidence: 91%
“…Potential risk factors for obesity in early life include genetic factors, lifestyle, and physical, health, and environmental conditions [12,13,14,15,16,17,18,19,20], which can all in turn be influenced by the family context and socio-economic factors [19,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Further, if either of the parents are overweight/obese the odds ratio rose to 3.10 (2.12-4.54). Compared to the present study, higher odds ratio were reported by studies conducted by Tchicaya et al, Ochoa MC et al, Shahin K et al, Zurrigga O et al and Farajain P et al 14,18,9,28,29 We also found weak correlations between parental body mass index and body mass index of their children in both the genders. Similar weak correlations were described by Sangha JK et al, Shahin K et al, Bralic et al, Fuiano N et al and Ochoa MC et al in both males and females.…”
Section: Discussioncontrasting
confidence: 51%
“…7 Various studies have been conducted across the world to find the association between the parental obesity and the obesity in their children. [8][9][10][11][12][13][14][15][16][17][18] But, there exists paucity of data of research in India. Further, the cut off for body mass index in adults used in studies outside India will not be generalizable to our country profile.…”
Section: Introductionmentioning
confidence: 99%
“…7 Tchicaya A et al study found children with obese parents have higher mean BMI and it's not related to the sex of the child. 8 Bahreynian M et al found in endocrinal study that males with overweight parents was comparatively 1.7 times more overweight than boys with normal-weight parents. Similarly, female child with overweight parents were more overweight compared to girls with normal-weight parents.…”
Section: Distribution Of Children Based On At Least One Overweight Pamentioning
confidence: 97%